2020
DOI: 10.3847/1538-4357/ab7a94
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Short GRB Pulses in the Fourth BATSE Catalog: Implications for the Structure and Evolution of the Jetted Outflows

Abstract: Considering the shortage of comparative studies on pulse temporal characteristics between singlepeaked short gamma-ray bursts (sGRBs) and double-peaked sGRBs, we examine the pulse properties of a sample of 100 BATSE sGRBs using the BATSE Time-Tagged Event (TTE) data with a 5-ms resolution. 243 individual pulses of the single-peaked, double-peaked and triple-peaked sGRBs are fitted to get their statistical properties such as the pulse asymmetry, amplitude, peak time, and pulse width, etc. For the double-peaked … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
2
17
1
Order By: Relevance
“…Additionally, Figure 15 (a1)(a2) illustrate that the f m values of the main peaks are generally larger than those of the other two components. On the other hand, the photon fluxes of main peaks and the other two components seem to be positively correlated, indicating that the luminosities of the main peaks are linked to those of the precursors and the EE components, agreement with the results of Zhang et al (2020) and von Kienlin et al (2019). Moreover, it in return hints that the three parts of prompt gamma ray emissions could be produced from the same progenitor.…”
Section: Main Peaks Versus Precursors or Eessupporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, Figure 15 (a1)(a2) illustrate that the f m values of the main peaks are generally larger than those of the other two components. On the other hand, the photon fluxes of main peaks and the other two components seem to be positively correlated, indicating that the luminosities of the main peaks are linked to those of the precursors and the EE components, agreement with the results of Zhang et al (2020) and von Kienlin et al (2019). Moreover, it in return hints that the three parts of prompt gamma ray emissions could be produced from the same progenitor.…”
Section: Main Peaks Versus Precursors or Eessupporting
confidence: 79%
“…Lien et al (2016) reported the fraction of sGRBs with EE to be 1.19% in the third Swift/BAT catalog. Here, we extend our search to include the GRBs with EE tails reported in literatures (e.g., Norris & Bonnell 2006;Kisaka et al 2017;Yu et al 2020;Zhang et al 2020). According to von Kienlin et al (2019), we adopt the following three criteria:…”
Section: Selection Criteria Of Precursor and Eementioning
confidence: 99%
“…It was found that the precursors are only slightly softer than the main bursts. Li et al (2020) obtained a short GRB precursor sample in the BATSE catalog. The angular spreading timescale and the cooling timescale were considered in the jet-cocoon scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we defined two kinds of double-peaked BATSE sGRBs as M-loose and M-tight types according to the overlapping ratios between two adjacent main peaks (see Fig. 1 in Li et al 2020a). Then we examined the temporal properties of the main peaks and the other two components of Swift/BAT sGRBs (Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%